Short-term exposure to nitrogen dioxide and outpatient visits for cause-specific conjunctivitis: A time-series study in Jinan, China. (15th February 2021) - Guo, Hui; Zhang, Shiyu; Zhang, Zhenwei; Zhang, Jing; Wang, Chongjian; Fang, Xinyu; Lin, Hualiang; Li, Huan; Ruan, Zengliang
Abstract: Background: Though the conjunctiva are directly contacting with the atmospheric environment, the association between air pollution and conjunctival disease has not been well documented. Objective: To explore the association between ambient nitrogen dioxide (NO2 ) and daily outpatient visits for cause-specific conjunctivitis in Jinan, China. Methods: Daily concentrations of air pollution were obtained from the air quality sharing platform of China, and daily outpatient visits for conjunctivitis were collected from Qilu Hospital. The association between daily NO2 level and outpatient visits for conjunctivitis was examined by a generalized additive Poisson model, and stratified analyses by sex, age and season were further performed. Results: A total of 42, 123 outpatient visits for conjunctivitis were recorded during 2014–2019, including 8504 infective conjunctivitis, 6429 allergic conjunctivitis and 27, 190 unspecified conjunctivitis. Each 10 μg/m 3 increase in NO2 was associated with a 1.00% (95% CI: 0.13%, 1.87%) increment in daily outpatient visits for conjunctivitis. Significant associations between NO2 and conjunctivitis were observed in the female population [excess risk, ER = 1.09% (95% CI: 0.05%, 2.15%)], in people aged 18–65 years [ER = 1.15% (95% CI: 0.15%, 2.15%)] and in cold season [ER = 1.67% (95% CI: 0.58%, 2.77%)]. Moreover, we also found significant associations of NO2 with infective conjunctivitis [ER = 2.60% (95% CI: 0.69%, 4.54%)], but not with allergic conjunctivitis [ER = −0.43% (95% CI: −2.38%, 1.56%)]and unspecified conjunctivitis [ER = 0.16% (95% CI: −0.96%, 1.29%)]. Conclusion: This study suggests that short-term exposure to NO2 might induce conjunctivitis, and air pollution control measures should be encouraged to keep ocular surface healthy. Highlights: Effects of NO2 on conjunctivitis and three specific subtypes were analyzed. Exposure to NO2 might induce conjunctivitis, especially the infective conjunctivitis. Associations were stronger in female, in people aged 18–65 years and in cold season.